Proliferation of bovine endometrial epithelial cells is promoted by prostaglandin E2-PTGER2 signaling through cell cycle regulation. (November 2021) - Liu, Bo; Fu, Changqi; Cao, Jinshan; Mao, Wei; Zhang, Shuangyi; Li, Qianru; Zhao, Jiamin; Feng, Shuang
Highlights: PGE2 -PTGER2 signaling promotes cell proliferation of bEECs. PGE2 -PTGER2 signaling promotes the expression of cyclins and CDKs in bEECs. PGE2 -PTGER2 signaling induces PCNA, COXs, PTGER2, and EGF expressions in bEECs. PGE2 -PTGER2 signaling-induced cell proliferation was blocked by CDK inhibitors. PGE2 -PTGER2 signaling could be involved in bovine endometrial growth/remodelling. Abstract: It is known that prostaglandin E2 (PGE2 ) induces proliferation of epithelia in bovine endometrial explants, however, the detailed mechanism of regulation of PGE2 in inducing bovine endometrial epithelial cell (bEEC) proliferation is unclear. In this study, we determined whether proliferation of bEECs is promoted by PGE2 -prostaglandin E receptor 2 (PTGER2) signaling activation through cell cycle regulation. The results demonstrated that bEECs proliferation was induced by treatment of PGE2 and PTGER2 agonist butaprost. These processes were down-regulated by PTGER2 antagonist AH6809 and CDK inhibitors (LEE011, CDK2 Inhibitor II and Ro 3306). PGE2 and butaprost induced cyclins (A, B1, D1, D3 and E2), cyclin-dependent kinases (CDKs, 1, 2, 4 and 6), and epidermal growth factor (EGF) expression were inhibited by AH6809 treatment in bEECs. Moreover, proliferating cell nuclear antigen (PCNA), cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), and PTGER2 expression in bEECs were up-regulated by PGE2 and butaprost treatment. Our data demonstrate that PGE2 -PTGER2 signaling activation has a direct molecular association with cell cycle regulation and cell proliferation in bEECs. Collectively, these findings will improve our understanding of the roles for PGE2 -PTGER2 signaling activation in the physiological and pharmacological processes of bovine endometrium.